Physical Activity and Colon Cancer: Timing, Intensity, and Sedentary Behavior - Boyle, Terry (2012)
Despite the convincing evidence that physical activity reduces the risk of colon cancer, there are some aspects of the association that remain unclear. These include the appropriate timeframe of exposure, whether the intensity of physical activity matters, and whether sedentary behavior is a distinct risk factor. This review summarized the research that has investigated these issues. In terms of timing, physical activity at any age (with the exception of physical activity performed up to and including the late teens) has been shown to be associated with a significantly reduced risk of colon cancer. Physical activity performed between 30 and 50 years of age, as well as long-term or lifetime physical activity, has been most consistently shown to reduce risk. For intensity, research to date suggests that more intense activity (particularly vigorous activity) may be associated with a greater reduction in the risk of colon cancer for males but not for females. Finally, most of the studies that have investigated the effect of sedentary behavior on the risk of colon or colorectal cancer have shown an increased risk, suggesting that sedentary behavior may be a distinct risk factor for colon cancer.